DIPLOMASI TAHTA SUCI VATIKAN UNTUK PERDAMAIAN DI TANAH SUCI - Maulana, Ana; Abel Josafat Manullang (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
The issue of Israel and Palestine has been going on for almost 70 years, and there is still no sign of lasting reconciliation. However, since 1948, several countries have taken part in the peace process between the two countries. Apart from state actors, non-state actors also contribute to Israeli-Palestinian reconciliation, one of which is the institution of the Catholic Church, the Holy See. With its unique status, the Holy See has a slightly different style of diplomacy. This difference can be seen in the presence of dual status, where the Holy See is both a state and a world religious institution. With the presence of this double-status, the Holy See has a wider diplomatic space than state actors, especially in conducting diplomacy related to the peacebuilding process. Therefore, this research aims to analyze the Holy See's diplomatic efforts in Israeli-Palestinian reconciliation. This research uses a qualitative approach by utilizing data sources from the internet and official documents. It finds that The Holy See plays a very important role in peace process in the Holy Land through religious institutions. It plays roles not only in bridging political friction between Israel and Palestine through normalizing relations, but also in undertaking humanitarian cases through social assistance.